Associations of leisure-time physical activity and active school transport with mental health outcomes: A population-based study - Jussila Juuso J; Pulakka Anna; Ervasti Jenni; Halonen Jaana I; Mikkonen Santtu; Allaouat Sara; Salo Paula; Lanki Timo (WILEY, 2025)
Promoting physical activity can improve population health. This study aimed to examine associations of leisure-time moderate-to-vigorous physical activity and active school transport with mental health, that is, symptoms of depression and anxiety, among 15- to 16-year-old adolescents. We also assessed the relationships with less-studied outcomes, such as chronic stress and visits to school psychologist. A nationwide Finnish cohort of eighth and ninth graders from the School Health Promotion study (32 829 participants; mean age 15.4 years; 53% girls) was studied. We used logistic regression to estimate odds ratios (OR), with models adjusted for major sociodemographic, health behavior, and physical activity variables. Key findings suggest that leisure-time moderate-to-vigorous physical activity is associated with better mental health in a dose-response manner. Even the smallest dose, 30 weekly minutes, was linked to 17% lower odds of chronic stress symptoms compared to inactivity (OR 0.83, 95% CI 0.71-0.96). Compared to non-active transportation, more than 30 min of daily active school transport yielded 19% (OR 1.19, 95% CI 1.07-1.31) and 33% (OR 1.33, 95% CI 1.12-1.58) higher odds of depression symptoms and school psychologist visits, respectively. However, no associations were found for low-to-moderate daily active school transport levels (<30 min). This large-scale study further highlights a positive association between leisure-time physical activity and mental health among youth. Future research should explore what factors might explain the potential adverse mental health outcomes of active school transport.